2019
DOI: 10.1111/ctr.13524
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer knowledge and photoprotective practices of organ transplant recipients

Abstract: Background: Long-term use of immunosuppressive medications by organ transplant recipients (OTRs) leads to an increased risk of non-melanoma skin cancers (NMSCs).The objective of this study was to assess photoprotective knowledge and practices among OTRs and to identify predictors of poor sunscreen adherence and barriers to photoprotection. Methods:A written survey was administered to 300 solid OTRs attending the Southern Alberta Transplant Program. Demographics, transplant and NMSC history, ultraviolet radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Due to the paucity of studies focusing on skin cancer risks in patients with GD, we hope that our findings will help fill the gap in the literature. The latter is a contrast to many prior studies on sun protection measures in organ transplant recipients around the world 20‐22,29,30 . Previous studies published in Australia did not include regional transplant recipients who overall have lower education attainment and employment opportunity which may affect patients' awareness of skin cancers and sun protection measures 16,19,26 .…”
Section: Discussionmentioning
confidence: 93%
“…Due to the paucity of studies focusing on skin cancer risks in patients with GD, we hope that our findings will help fill the gap in the literature. The latter is a contrast to many prior studies on sun protection measures in organ transplant recipients around the world 20‐22,29,30 . Previous studies published in Australia did not include regional transplant recipients who overall have lower education attainment and employment opportunity which may affect patients' awareness of skin cancers and sun protection measures 16,19,26 .…”
Section: Discussionmentioning
confidence: 93%
“…Male sex has previously been reported as a risk factor for skin cancer in OTRs 24 . This may relate, in part, to photoprotective behavior and occupational UVR exposure 25,26 …”
Section: Discussionmentioning
confidence: 97%
“…Studies in North America, Europe and Australia have found sun protective measures in SOTRs were suboptimal. [37][38][39] Patient compliance with photoprotective measures, based on observational studies and randomized control trials (RCTs), would improve if education was reinforced after immunosuppressant exposure. [40][41][42][43][44][45][46][47][48][49][50][51]…”
Section: Risk Factors Of Skin Cancersmentioning
confidence: 99%